MUSIK INDIEBAGI KALANGAN REMAJA DI KOTA DENPASAR Studi Tentang Antropologi Kesenian - Kusuma, I Dewa Gede (Humanis; Volume 4. No. 1. Juli 2013, 2013)
This research entitled "Indie Music for Teenagers in Denpasar" with the problems of study: 1) how the profile of Indie music in Denpasar is, 2) the factors of teenagers in Denpasar like Indie music, 3) how Indie music on the implications of the behaviour of teenagers in Denpasar. The foundation of theory used in this research is the theory of the function of Alan P. Merriam and the aesthetic theory of Beardsley. This research is qualitative research approach. The informants in this research consist of 6 bands and 6 teenagers that is specified by pusposive sampling. The results of the study are: 1) the profile of Indie music in Denpasar is embodied in the form of the band, which until now research amounted 78 Indie bands. Indie music in Denpasar can not be released from the culture background of Balinese artistic activity since childhood honed by sekaa-sekaa or artistic activity groups, 2 Indie music is able to provide entertainment, creativity and expression of teenagers. Indie music entertainment provides the space of teenagers creativity in music form and to refine the soul through music. 3) the implications of Indie music to teenagers behaviour, in a positive youth increasingly creative and innovative as well as fostering the spirit of Indie music to be an entrepreneur because through growing creative economy efforts in the field of sound system, clothing and merchaindase, while the negative implications are teenagers forget traditional art, the affected alcohol and tattoo culture.
Keywords: art, indie music, teenagers